An Examination Of Shareholders Wealth Effects of Mergers And Acquisitions - The Hong Kong Evidence - Huang, Lishan (2009)
This dissertation concentrates on examining the shareholders wealth effects of mergers and acquisitions in the Hong Kong stock market. By taking a data sample of 31 companies out of the 42 listed companies in the Hang Seng Index during an 18-month period from 01/02/2007 to 01/08/2008, this study provides a discussion on the share price performance of bidding companies and target companies, leading to an analysis of the shareholders wealth effects from mergers and acquisitions activities.